The additive effect of herbal medicines on lifestyle modification in the treatment of non-alcoholic fatty liver disease: a systematic review and meta-analysis - Kim, Myung-Ho; Ahn, Subin; Hur, Nayeon; Oh, Seung-Yun; Son, Chang-Gue (Frontiers in Pharmacology, 2024)
Non-alcoholic fatty liver disease (NAFLD) is difficult to manage because of its complex pathophysiological mechanism. There is still no effective treatment other than lifestyle modification (LM) such as dietary modifications, regular physical activity, and gradual weight loss. Herbal medicines from traditional Chinese Medicine and Korean Medicine have been shown to be effective in the treatment of NAFLD based on many randomized controlled trials. This systematic review and meta-analysis aims to evaluate the additive effects of herbal medicines on LM in the treatment of NAFLD. Two databases (PubMed and Cochrane library) were searched using keywords related to NAFLD and herbal medicines. Then the randomized controlled trials (RCTs) evaluating the therapeutic effects of herbal medicines combined with LM were selected. The pooled results were analyzed as mean difference (MD) with 95 % confidence interval (CI) for continuous data, and risk ratio (RR) with 95 % CI for dichotomous data. Eight RCTs with a total of 603 participants were included for this review study. Participants were administered with multi-herbal formulas (Yiqi Sanju Formula, Tiaogan Lipi Recipe, and Lingguizhugan Decoction) or single-herbal extracts (Glycyrrhiza glabra L., Magnoliae offcinalis, Trigonella Foenum-graecum L. semen, Portulaca oleracea L., and Rhus Coriaria L. fructus) along with LM for 12 weeks. The meta-analysis showed a significant improvement in ultrasound-based liver steatosis measured by odds ratio (OR) in the herbal medicine group than those with LM alone (OR = 7.9, 95 % CI 0.7 to 95.2, P<0.1). In addition, herbal medicines decreased the levels of aspartate transferase (MD -7.5, 95 % CI -13.4 to -1.7, P=0.01) and total cholesterol (MD -16.0, 95 % CI -32.7 to 0.7, P=0.06) more than LM alone. The meta-analysis partially showed clinical evidence supporting the additive benefits of herbal medicines for NAFLD in combination with LM. Whereas, it is necessary to provide a solid basis through higher-quality studies using a specific herbal medicine.